Importance of wash riding in kayaking training and competition - Perez-Landaluce, J.; Rodriguez-Alonso, M.; Fernandez-Garcia, B.; Bustillo-Fernandez, E.; Terrados, N. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: The use of different wash-riding techniques is common during kayak training and competition. Changes in wash-riding positions could imply a different exercise intensity. The aim of this study, therefore, was to quantify the energy savings made when a kayaker is "wash riding." METHODS: Eight male international flat water kayakers, who performed a field test of 2000 m in each of the four wash-riding positions, head (H), right wave (RW), left wave (LW), and end position (V), were studied. The data investigated were: time, stroke rate, blood lactate (BL), heart rate (HR), and rate of perceived exertion (RPE). Under laboratory conditions kayakers performed the same intensity of exercise in a kayak ergometer, and HR, oxygen uptake (VO2), BL, mean power output (W), and RPE were measured. RESULTS: The results show significant differences (P < 0.05) among H, RW/LW, and V. The mean values for BL (P < 0.05) were 4.2, 2.0, 2.2, and 1.5 mmol.L-1, for H, RW, LW, and V, respectively. RPE also revealed differences, with values of 15, 12.6, 12.6, and 9.7 for H, RW, LW, and V, respectively. Mean power output gave values of 190.3 (H), 155.6 (RW and LW), and 129.5 (V) W. HR was different between H and V (172 and 151), while stroke rate was different among the parameters H, RW, and V (93.7, 88.8, and 87.6, respectively). The VO2 in the kayak ergometer test showed a difference between H and V (3.78 and 2.23 L.min-1). CONCLUSIONS: We conclude that "wash riding" involves a saving in energy cost of between 18% and 31.9%, depending on the position. This conclusion is of importance for the quantification and calibration of kayak training and competition.